2020
DOI: 10.3389/fpsyg.2020.568073
|View full text |Cite|
|
Sign up to set email alerts
|

Neural Correlates of Theory of Mind Are Preserved in Young Women With Anorexia Nervosa

Abstract: People with anorexia nervosa (AN) commonly exhibit social difficulties, which may be related to problems with understanding the perspectives of others, commonly known as Theory of Mind (ToM) processing. However, there is a dearth of literature investigating the neural basis of these differences in ToM and at what age they emerge. This study aimed to test for differences in the neural correlates of ToM processes in young women with AN, and young women weight-restored (WR) from AN, as compared to healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 39 publications
1
28
1
Order By: Relevance
“…Data were extracted from three existing data sets. AN, REC, and TD participants were from two studies investigating social and emotional functioning in AN [ 28 , 42 ], while participants with ASD were from the European Autism Interventions Longitudinal European Autism Project (EU-AIMS LEAP) [ 43 ]. Details regarding participant recruitment for the original studies can be found in the Additional file 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Data were extracted from three existing data sets. AN, REC, and TD participants were from two studies investigating social and emotional functioning in AN [ 28 , 42 ], while participants with ASD were from the European Autism Interventions Longitudinal European Autism Project (EU-AIMS LEAP) [ 43 ]. Details regarding participant recruitment for the original studies can be found in the Additional file 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, 40% of adolescents with AN had broader autism phenotype ( 45 ) and 26% of adults with AN had autistic features ( 46 ). It is thought that there may be a common pathogenesis between the AN and ASD, because some symptoms of ASD are observed in AN, such as misunderstanding social clues, difficulties in processing social information and providing appropriate response in interpersonal communication, and obsessive-compulsive features ( 9 , 47 ). Similar to those results in the literature, the findings of this study showed that the social awareness, social cognition, communication and social motivation are impaired in adolescents with AN, indicating that there may be a common pathogenesis between AN and ASD.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies over the past few years documenting the relationship between AN and ASD, first identified by Gillberg in 1983 ( 8 ). Both conditions share a common profile of resistance to changes, social withdrawal and social disengagement, and show similar patterns of neurocognitive dysfunction including impaired set-shifting, weak central coherence, and impaired theory-of-mind (ToM) abilities ( 6 , 9 ). Patients with AN have also poor social and emotional functioning ( 10 , 11 ), including interpersonal relationship problems ( 7 ), reduced facial emotion expression ( 12 ), impaired facial emotion recognition ( 13 ), difficulties identifying emotions ( 10 ) and social anhedonia ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have challenged their findings reporting no difficulties in theory of mind or facial affect recognition among people with AN (Dapelo et al, 2015;Ambwani et al, 2016;Kerr-Gaffney et al, 2020;Leslie et al, 2020). Some of the studies suggested that the previous reported findings of emotion recognition difficulties may reflect negative interpretation biases when labelling emotions (Dapelo et al, 2015;Ambwani et al, 2016).…”
Section: Introductionmentioning
confidence: 92%